Sex-Differences, Handedness, and Lateralization in the Iowa Gambling Task - Singh, Varsha (Frontiers in Psychology, 2016)
In a widely used decision-making task, the Iowa Gambling Task (IGT), male performance is observed to be superior to that of females, and is attributed to right lateralization (i.e., right hemispheric dominance). It is as yet unknown whether sex-differences in affect and motor lateralization have implications for sex-specific lateralization in the IGT, and specifically, whether sex-difference in performance in the IGT changes with right-handedness or with affect lateralization (decision valence, and valence-directed motivation). The present study (N = 320; 160 males) examined the effects of right-handedness (right-handedness vs. non-right-handedness) as a measure of motor lateralization, decision valence (reward vs. punishment IGT), and valence-directedness of task motivation (valence-directed vs. non-directed instructions), as measures of affective lateralization on IGT decision making. Analyses of variance revealed that both male and female participants showed valence-induced inconsistencies in advantageous decision-making; however, right-handed females made more disadvantageous decisions in a reward IGT. These results suggest that IGT decision-making may be largely right-lateralized in right-handed males, and show that sex and lateralized differences (motor and affect) have implications for sex-differences in IGT decision-making. Implications of the results are discussed with reference to lateralization and sex-differences in cognition.